GLOBALIZATION IN RELATION TO NATIONAL AND LINGUISTIC IDENTITY - CAMELIA NEAGU (Challenges of the Knowledge Society, 2013)
As an international language used for global, political, cultural and financial exchange, the English language teaching in promoting globalization has been approached from diverse views. The paper intends to investigate the most used terms for globalization since Western countries or the United Nations are now considered the super power with a leading economic, cultural and military position in the global order and, of course, with many of the most apparently cultural expressions of globalization. As English has been the prevailing foreign language in the curricula of educational institutions, it is accepted as the dominating language in the world for globalization comes to be commonly known in political and educational communication.